1982
DOI: 10.1163/002829683x00066
|View full text |Cite
|
Sign up to set email alerts
|

The Competition Between Asobara Tabida Nees Von Esenbeck, 1834 and Leptopilina Heterotoma (Thomson, 1862) in Multiparasitized Hosts

Abstract: The course of competition between the solitary endoparasitoids Asobara tabida Nees von Esenbeck, 1834 and Leptopilina heterotoma (Thomson, 1862) in multiparasitized hosts (Drosophila melanogaster Meigen, 1830 and D. subobscura Collin, 1936) was followed in time. The outcome of competition was determined, as well as the mechanisms used by the parasitoids to eliminate a competitor and the moment at which this elimination occurred. The effect of various intervals between oviposition periods, of various temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 0 publications
0
20
0
1
Order By: Relevance
“…Van Strien -van Liempt (1983) observed physical attack between L. heterotoma and Asobara tabida and also the existence of a physiological mechanism of elimination. A similar process may be present in the interspecies competition studied here.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Van Strien -van Liempt (1983) observed physical attack between L. heterotoma and Asobara tabida and also the existence of a physiological mechanism of elimination. A similar process may be present in the interspecies competition studied here.…”
Section: Discussionmentioning
confidence: 89%
“…Although laboratory studies suggest that the outcome of competition may be determined by the sequence of attacks (Fisher 1961, Force and Messenger 1968, Wallner et al 1982, van Strien -van Liempt 1983 or intrinsic superiority of one species over another (Vinson and Ables 1980, Pintureau et al 1980, Sorokina 1983, field mechanisms of competition between species are inconclusive. That parasitoids sometimes compete in the field is strongly suggested, especially through "interference" competition, corresponding to direct harm to one species by another.…”
Section: Introductionmentioning
confidence: 99%
“…Sympatric parasitoid species that share the same host species may be competitors (Van Strien-van Liempt, 1983). The greater the part of the host population that is exploited by both species, the more they will affect each other's population density.…”
Section: Discussionmentioning
confidence: 99%
“…The greater the part of the host population that is exploited by both species, the more they will affect each other's population density. Their competitive abilities then, among other factors, determine their relative abundance (Van Strien-van Liempt, 1983). According to Dent (1995), when two species compete with one another intensely enough over limited resources, then with time, one or the other can become extinct.…”
Section: Discussionmentioning
confidence: 99%
“…Schroder, 1974;Weseloh, 1979;van Strien-van Liempt, 1983), one of the 2 parasitoids being killed within a few days. Van Strien-van Liempt (1983) found that in the interaction between the braconid Asobara tabida (Nees) and the cynipid Leptopilina heterotoma (Thomson), the outcome was dependent not only on the interval between the 2 ovipositions, but also on environmental conditions and the larval age of the host. In the present study, the outcome of the interaction between A. bilineata and T. rapae appeared to depend on the state of the eucoilid's development at the time at which A. bilineata attacked.…”
Section: Discussionmentioning
confidence: 99%